Variáveis ecofisiológicas do tronco como indicadores de sustentabilidade da floresta tropical manejada seletivamente - Teixeira, Liliane Martins (Instituto Nacional de Pesquisas da Amazônia – INPA, 2010)
The better understanding of forest functioning in the context of carbon exchange with atmosphere and the responses of remaining forest at the harvesting impacts induce at the study of individual responses of trees at different intensities of forest harvest. Physiological variables like respiration of wood tissue, diameter growing and the isotopic rate can provide indicatives of health of selective managed forest. The aim of this study was to evaluate the influence of selective logging in the monthly current increment of diameter (ICM), in the respiration flux of trunk (RESP) and the carbon (d13C) and nitrogen (d15N) isotopic rate of remaining trees in a terra-firme forest in the Manaus Region/AM/Brazil. It was allocated 3 experimental blocks of 1 ha (two intensities of logging light and hard and the control treatment), where 16 trees per treatment, adding up 48 trees. It was randomly chose three class of diameter. For these trees, it was accompanied the ICM (with use of metallic dendrometers) and the PRESP (with IRGA) for 24 months, during 12 months before and after of exploitation. It was collected foliar and wood tissue samples of each one study-tree in the 12° month after exploitation for d13C e d15N analyses, with use of mass spectrometrum (Delta Plus, Finnigan MAT). The relationship of precipitation with ICM was not influenced by logging (r = -0.03; and r = -0,15, for B1 and B3 with p = 0,999). The RESP was positively correlated with more logging intensity (r = 0.68; p = 0,086). The lesser logging intensity increased in 68% the relationship with ICM and RESP. The d13C of wood tissue was positively and significantly correlated with diameter class (r = 0.592; p = 0.0000), the same occurred for foliar tissue (r= 0.503; p = 0.01). It has differences between treatments of wood tissue (p < 0.01), while for foliar tissues, the difference was verified between B3 and the control block (p = 0,0059). The RESP was significantly and dependently related with DAP, ICM, d13C e d15N (p < 0,001). However, if we consider the costs of analyze and collection, the relation lnRESP = f (lnICM) is better (p < 0.0000). The logging treatments influenced the behavior of managed forest when to compare with no logging forest, with the same environmental. This influence was more perceptible for trees with lesser diameters, which can compromise the survivor of young remaining trees. Hence, for a new cycle of exploitation, treatments conduction of remaining trees become essential for the recompose the timber supply of managed forest.
Keywords: Ecofisiologia; Floresta tropical; Manejo florestal; Exploração seletiva